Minimum deterrence and India's nuclear security - Basrur, Rajesh M (Studies in Asian security, 2006)
In this book, the leading authority on India's nuclear program offers an informed and thoughtful assessment of India's nuclear strategy. Basrur shows that the country's nuclear culture is generally in accord with the principle of minimum deterrence but sometimes drifts into a more open-ended view.